Evaluation of methods for measuring microbial biomass C and N and relationship between microbial biomass with soil organic matter particle size classes in West African soils - Vanlauwe, Bernard; Nwoke, O.C.; Sanginga, N.; Merckx, Roel (1999)
The fumigation–incubation (FI) and the fumigation–extraction (FE) ninhydrin methods for quantifying the microbial biomass pool were tested and the relationships between microbial biomass characteristics and soil organic matter fractions (separated following particle size) investigated for a range of soils representative for the West-African moist savanna zone (13 soils). Three soils from the humid forest zone were also included. Microbial C values calculated using the CO2-C production of the fumigated soils from d 10 to d 20 as control (Bio-C (II)) were better correlated with the flush of ninhydrin reactive N (NRN) during 10 d of fumigation than those calculated with the CO2-C production in the unfumigated soils from d 10 to d 20 as control (Bio-C (I)). The Bio-C (II) values also showed a more consistent range of values (22–210 mg C kg−1 soil) than the Bio-C (I) values. Using a kC factor of 0.35, which was considered to be more appropriate for our soils than a kC factor of 0.45, kC,NRN could be estimated as 22 and 16, for a 5- and 10-d fumigation, respectively. For all savanna soils, the NRN flush after 5 d of fumigation was closely related to the NRN flush after 10 d, indicating that a 5-d fumigation was sufficient provided that the k-values are adapted. Mineral N flushes during incubation and incubation after fumigation were small. Although microbial N values calculated as [NH4+-N flush of the fumigated soils (0–10 d)]/kN with kN=−0.014×(CO2-C-flush-to-NH4+-N-flush during fumigation)+0.39, which gave values of 14.0–100.7 mg N kg−1 soil, showed the best relationship with the NRN flush after 10 d of fumigation, microbial N values calculated as [(mineral N flush of the fumigated soils after 10 d)−(mineral N flush of the unfumigated soils after 10 d)]/0.68, which gave values of 3.4–46.2 mg N kg−1 soil, including 3 values <2 mg N kg−1 soil and 1 negative value, yielded microbial C-to-N ratios (4.7–16.4) which were better reflecting the ratio C-flush-to-N-flush of fumigated soils (5.2–13.5). Using a kN value of 0.68, kN,NRN could be estimated as 1.5. Between 7 and 17% and between 11 and 28% of the total soil C was part of the soil litter (SL) (organic particles larger than 250 μm) and the particulate organic matter (POM) (organic particles larger than 53 μm), respectively. The CO2-C production of the unfumigated soils was strongly (P<0.01) related to the SL-C content. Inclusion of the silt and clay content in a linear regression equation increased the R2 value from 0.70 to 0.91. The Bio-C (II) content showed the best relationship with the C content of the soil particles between 53 and 20 μm and the silt fraction. The NRN flush after 10 d showed the best relationship with the C content of the particles between 250 and 53 μm and between 53 and 20 μm. Maximally 48% of the variation in Bio-C (II) values was explained by the C content of the various fractions, indicating that the present methods do not exclusively measure the active microbial biomass.